Influence of Green Infrastructure on Residents’ Endorsement of the New Ecological Paradigm in Lagos, Nigeria - Dipeolu, Adedotun Ayodele; Ibem, Eziyi Offia; Oriola, Olusegun Ayotunde (Journal of Contemporary Urban Affairs, 2022)
Given the significance of green infrastructure in enhancing social, economic and ecological sustainability of the built environment, it is important to unearth how green infrastructure can influence pro-environmental behaviours among the urban population. This research assessed the influence of green infrastructure on residents’ endorsement of the New Ecological Paradigm (NEP) in Lagos Metropolis, Nigeria. A total of 1560 residents recruited through the multi-stage sampling technique participated in the survey, and the data gathered were subjected to descriptive and regression analyses.  The participants generally felt that the available green infrastructure in their neighbourhoods was of low quality and rapidly disappearing, but it positively influenced all the key variables of the NEP and its endorsement. The size of neighbourhood green spaces, availability of green spaces for relaxation and its proximity to the people were found to be the three attributes of green infrastructure with the most noticeable influence on residents’ endorsement of NEP. This study implies that the availability and accessibility of a reasonable quantity of green areas within urban neighbourhoods can enhance a better understanding of the role of green infrastructure and promote favourable environmental behaviours among the urban population within and outside Nigeria.